Programa trabajo en equipo para lograr compromisos de la gestión escolar en los docentes de la institución educativa Teniente Manuel Clavero Muga Punchana 2024 - Rengifo Garcia, Bertha (2025)
The study evaluated the effect of a "teamwork" educational program to achieve school management commitments in the teachers of the Teniente Manuel Clavero Muga educational institution, Punchana, using an evaluative, quasi experimental design, working with a sample of 60 teachers of the educational institution. It was determined that at the Teniente Manuel Clavero Muga Educational Institution, the "teamwork of teachers" program is linked to the commitment: annual progress of student learning with (p=0.043), with the annual retention of students with (p=0.000), with compliance with the planned scheduling with (p=0.001), with the accompaniment and monitoring of the pedagogical practice of students with (p=0.028), with the management of school coexistence with (p=0.000). The "teamwork" program has a rating of three (3) relatively agreeing, The organization of the program has rating three (3) that is relatively agreeing and agreeing with the operation of the Program. it was concluded that the educational program "teamwork" has a significant effect on the achievement of the commitments of school management in the teachers of the Teniente Manuel Clavero Muga educational institution, Punchana 2024.